Development of biomimetic and smart coatings based on elastin-like polymers containing RGD cell attachment sequences - Costa, R. R. (2008)
[Excerpt] Elastin-like polymers (ELPs) are based on repeating sequences found in the natural elastin. They show remarkable combination of properties, such as a large range of mechanical properties, excellent biocompatibility, and smart behaviour and self-assembly towards temperature, pH and often different stimuli. Around a certain temperature, known as inverse transition temperature (ITT) these polymers show phase transitions aqueous solutions: under the ITT, the polymer chains are disordered and in a relatively extended state, remaining soluble; above the ITT, the chains suffer a transition to a helical ordered state and aggregate. Nowadays, through recombinant genetic engineering it is possible to construct and produce recombinant ELPs with specific cell attachment sequences from human fibronectin and elastin. [...]